A Temporary Liminal Space Counteracting the Permanent ‘in between’ in Working Life - Vesala, Hanne; Tuomivaara, Seppo (Nordic Journal of Working Life Studies, 2019)
Ambiguous liminality used to exist ‘in between’, in a transition to a new social-structural order, but recently, it has gained a more permanent and normalized presence in working life, where existing boundaries are becoming blurred. However, liminality as a continuous state can be individually demanding. This paper elaborates upon a theoretical understanding of permanent and temporary liminality in working life and examines possible measures to tame excessive liminality. To illustrate the theoretical development, forms of permanent and temporary liminality in the lives of three professionals are analyzed. We found that dealing with multiple and complex work roles independently could be conducive to fracturing work routines, which we identify as habitualized, permanent liminality. Withdrawal to an alternative work environment – a rural Finnish archipelago – formed a liminal space in its original sense, a creative and reflective phase that illuminated work-related challenges. It is suggested that such spaces are designed to achieve simplicity.